Granulocyte-Macrophage Colony Stimulating Factor in Single Blastocyst Conditioned Medium as a Biomarker for Predicting Implantation Outcome of Embryo - Chen, Peilin; Huang, Chunyu; Sun, Qing; Zhong, Huixian; Xiong, Feng; Liu, Su; Yao, Zhihong; Liu, Zhiqiang; Wan, Caiyun; Zeng, Yong; Diao, Lianghui (Frontiers in Immunology, 2021)
Background It is highly desirable to develop new strategies based on secretomics to more accurately selection of embryos with the highest developmental potential for transfer. Granulocyte-macrophage colony-stimulating factor (GM-CSF) has been reported to promote embryo development and pregnancy establishment. However, the predictive value of GM-CSF in single blastocyst selection remains unclear. This study is to determine the concentration of GM-CSF in human single-blastocyst conditioned medium (SBCM) and to evaluate its association with embryo quality and pregnancy outcome. Methods The patients with ≤38 years of age receiving the first cycle of assisted reproductive therapy were included in this study. The patients who had <4 top-quality embryos formed by the fertilized two pronuclear zygotes on day 3 were excluded. A total of 126 SBCM samples (SBCMs) were included, of which blastocysts from 77 SBCMs were later transferred in subsequent frozen-thawed embryo transfer. The concentrations of GM-CSF were detected by single-molecule array (SIMOA) and analyzed for their possible association with embryo quality and pregnancy outcomes. The top-quality embryo (TQ), positive HCG (HP), clinical pregnancy (CP), and ongoing pregnancy (OP) rates were determined and compared between groups divided based on GM-CSF concentrations. Results The detection rate of GM-CSF was found to be 50% in all SBCMs. There were significant differences in TQ rate, HP rate, CP rate and OP rate among high concentration group, medium concentration group and low concentration group. Both GM-CSF alone or GM-CSF combined with the morphological score (MS) had a greater AUC of ROC curve than that of MS alone to predict the pregnancy outcome, and GM-CSF combined with MS had the highest AUC. Conclusions The concentration of GM-CSF in SBCM was detected at fg/ml levels, which was associated with embryo quality and pregnancy outcome. Collectively, GM-CSF may be used as a biomarker for prediction of pregnancy outcome and selection of embryos with high developmental potential for transfer in assisted reproductive technology (ART).